PENGARUH ROA DAN TOBIN’S Q TERHADAP VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Indra Saputra (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This purpose of this study was to found whether effect Return On Asset (ROA) dan Tobin’s Q against the Trading Volume Activity (TVA) within mining company which registered in Indonesia Stock Echange listed from 2011 to 2014, because 4 (four) consecutive years mining companies in Indonesia experience fluctuation. The sample drawn by purposive sampling and fulfill sample selection criteria. Method of data analysis using multiple linear regression. The result of research partially Return On Asset (ROA) ROA has no effect on Trading Volume Activity (TVA) and Tobin's Q effect on Trading Volume Activity (TVA), simultaneously states that ROA and Tobin's Q variables affect Trading Volume Activity (TVA). While R square Return On Asset (ROA) and Tobin's Q influence on Trading Volume Activity (TVA) only 41% only and the rest influenced by variable or other factors.